Persepsi Petani Terhadap Peranan Penyuluh Pertanian dalam Pengembangan Kelompok Tani di Kecamatan Gedong Tataan Kabupaten Pesawaran - Alfatih, Muhammad Fadlan; Soepratikno, Serly Silviyanti; Effendi, Irwan (Suluh Pembangunan : Journal of Extension and Development, 2024)
The role of agricultural extension workers in developing farmer groups is important in order to improve the mindset, attitude and ability of farmers to absorb information, innovation and technology, thus creating independent farmers. Therefore, the government's attention is very much needed in facilitating extension support facilities and increasing the number of extension workers so that equitable agricultural development can be realized. The purpose of this study was to determine the level of farmers' perceptions of the role of extension workers in the development of farmer groups in Gedong Tataan District, Pesawaran Regency. Data collection in this study was carried out in July 2022-August 2022. Respondents in this study were 97 members of farmer groups. This study uses a survey method and a purposively determined location with a quantitative descriptive approach. The results of this study are the level of farmers' perceptions of the role of extension workers in Gedong Tataan District with the development of farmer groups, namely the role of mentors is in the high category, the level of farmers' perceptions of the role of extension workers as organizers, dynamists, liaison liaisons and is in the medium category.